2023
DOI: 10.3389/fendo.2023.1143067
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular and macrovascular complications of type 2 diabetes mellitus: Exome wide association analyses

Abstract: BackgroundType 2 diabetes mellitus (T2DM) is a chronic, metabolic disorder in which concomitant insulin resistance and β-cell impairment lead to hyperglycemia, influenced by genetic and environmental factors. T2DM is associated with long-term complications that have contributed to the burden of morbidity and mortality worldwide. The objective of this manuscript is to conduct an Exome-Wide Association Study (EWAS) on T2DM Emirati individuals to improve our understanding on diabetes-related complications to impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 90 publications
0
13
0
Order By: Relevance
“…These complications are a significant cause of morbidity and mortality in T2DM patients [3]. Microvascular complications are associated with a longer duration of diabetes and higher levels of glycated hemoglobin (HbA1c) [10]. Therefore, early detection and management of microvascular complications are crucial in the care of patients with T2DM.…”
Section: The Link Between Microvascular Complications and T2dmmentioning
confidence: 99%
“…These complications are a significant cause of morbidity and mortality in T2DM patients [3]. Microvascular complications are associated with a longer duration of diabetes and higher levels of glycated hemoglobin (HbA1c) [10]. Therefore, early detection and management of microvascular complications are crucial in the care of patients with T2DM.…”
Section: The Link Between Microvascular Complications and T2dmmentioning
confidence: 99%
“…However, with the listed discovery cohorts being mostly of European ancestry and individual polymorphisms having only small effects, it is not surprising that most of the associations were not replicated in validation cohorts of different ethnic backgrounds [ 80 ]. For example, rs136161 located in the Apolipoprotein L1 coding gene (APOL1), one of the loci linked to DKD across multiple ethnic groups [ 81 ], was recently replicated in a relatively small study cohort from the Genome Database of the Latvian Population [ 82 ] but was not replicated in another small cohort from the Emirati population [ 83 ].…”
Section: Molecular Mechanisms and Molecular Genetics Of Sglt Action—p...mentioning
confidence: 99%
“…13 Severe complications, including hyperglycemia and microvascular and macrovascular complications, are associated with impaired glucose uptake in the skeletal muscle of patients with T2DM. 14 At the cellular level, it has been reported that sulfonylureas and metformin enhance insulin-mediated glucose utilization in muscle tissue by a distal mechanism to the insulin receptor. 15,16 Sulfonylurea drugs are recommended as a second-line therapy for T2DM management.…”
Section: Introductionmentioning
confidence: 99%
“…13 Severe complications, including hyperglycemia and microvascular and macrovascular complications, are associated with impaired glucose uptake in the skeletal muscle of patients with T2DM. 14…”
Section: Introductionmentioning
confidence: 99%